Pemberian Edukasi Tentang Kompres Hangat untuk Mengurangi Nyeri Punggung pada Ibu Hamil Trimester III - Bella Riska Ayu (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
Pregnancy is a natural and normal process. In the period of gestation, expectant mothers often experience discomfort such as back pain. There are various treatments to treat back pain, namely pharmacological and non-pharmacological. Pharmacological therapy generally consists of the administration of drugs that can have negative effects on the mother, fetus and delivery process. Therefore, non-pharmacological therapies such as warm compresses are more advisable because they are cheaper, safer, effective, and without adverse effects. The purpose of this community service is to improve the knowledge of pregnant women in the third trimester in the management of back pain using warm compresses during pregnancy. This activity was carried out through lecture and question and answer methods, as well as providing leaflets to participants in the management of back pain using warm compresses during pregnancy. Before the extension activities started we did pre-test and post-test after the extension activities. Counseling activities were carried out at The Independent Practice of Midwives (PMB) Yuli Bahriah Palembang city which was attended by 16 Pregnant Women. As a result of the implementation of this activity, the participants were very enthusiastic about the material that had been delivered by the presenters during the activity. The evaluation results obtained from the post-test results showed that knowledge about the management of back pain using warm compresses during pregnancy increased by 56.25% of the number of participants who were able to answer questions on the counseling material presented. In conclusion, the provision of education on the management of back pain using warm compresses can have a positive impact on pregnant women so that they can understand and implement the provision of warm compresses when experiencing back pain during pregnancy.